A before‐and‐after observational study of a protocol for use of the C‐MAC videolaryngoscope with a Frova introducer in pre‐hospital rapid sequence intubation. (8th January 2018) - Ångerman, S.; Kirves, H.; Nurmi, J.
Summary: Results using videolaryngoscopy in pre‐hospital rapid sequence intubation are mixed. A bougie is not commonly used with videolaryngoscopy. We hypothesised that using videolaryngoscopy and a bougie as core elements of a standardised protocol that includes a drugs and a laryngoscopy algorithm would result in a high first‐pass tracheal intubation success rate. We employed videolaryngoscopy (C‐MAC) combined with a bougie (Frova intubating introducer) in an anaesthetist‐staffed helicopter emergency medical service. Data for adult tracheal intubation were collected prospectively as part of the airway registry of our unit for 22 months after implementation of the protocol (n = 543) and compared with controls (n = 238) treated in the previous year before the implementation. The mean first‐pass success rate (95%CI) was 98.2% (96.6–99.0%) in the study group and 85.7% (80.7–89.6%) in the control group, p < 0.0001. Combining C‐MAC videolaryngoscopy and bougie with a standardised rapid sequence induction protocol leads to a high first attempt intubation success rate when performed by an anaesthetist‐led helicopter emergency medical service team.